1975
DOI: 10.1243/jmes_jour_1975_017_040_02
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Reynolds Equation for Micropolar Lubricants and its Application to Optimum One-Dimensional Slider Bearings: Effects of Solid-Particle Additives in Solution

Abstract: The effects of solid-particle additives in the lubricant are considered by characterizing this suspension as a micropolar fluid. The generalized Reynolds equation for this case has been derived and the optimum one-dimensional slider bearing is studied by using the techniques of the calculus of variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…The rate of lubricant flow discharging from the two ends of the bearing is determined from Qz= C (15) The integration is carried out along the film thickness. The dimensionless expression corresponding to Eq.…”
Section: Pressure Induced Flow Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of lubricant flow discharging from the two ends of the bearing is determined from Qz= C (15) The integration is carried out along the film thickness. The dimensionless expression corresponding to Eq.…”
Section: Pressure Induced Flow Termsmentioning
confidence: 99%
“…Allen and Kline [1] considered a two-dimensional flow field of micropolar fluids and applied it towards the problem of bearings. Shukla and Isa [15] derived the generalized Reynolds equation for micropolar fluids with application to one-dimensional slider bearings. Prakash and Sinha [14] considered the infinitely long journal bearing with micropolar fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators used the micropolar fluid theory for the study of several bearing systems. The generalized Reynolds equation for micropolar lubricants is derived by Shukla and Isa [13]. They found that the maximum load carrying capacity and corresponding frictional force increase with increase of the parameter characterising the microstructure imparted to the lubricants by the presence of additive.…”
Section: Introductionmentioning
confidence: 99%
“…In 1972, Eringen [2] also proposed the theory of thermomicro fluids, and succeeded in interpreting the behavior of some kinds of non-Newtonian fluids. In 1975, Shukla and Isa [3] presented the generalized Reynolds equation for micropolar fluids with the application to one-dimensional slider bearings. Meanwhile, Prakash and Sinha [4] analyzed the infinitely long journal bearing, with the lubrication of micropolar fluids.…”
mentioning
confidence: 99%